2022
DOI: 10.1007/s11292-022-09536-8
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of physical activity interventions in reducing antisocial behavior: a meta-analytic review

Abstract: Objectives This systematic review and meta-analysis examines the efficacy of physical activity interventions in the reduction of antisocial behavior in children and adults. Several possible moderators, including study design, sample characteristics (age, proportion male, and sample type), control group, and outcome characteristics (type of activity, duration, frequency), were also investigated. Methods A literature search was performed in the following dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 103 publications
1
10
0
Order By: Relevance
“…Furthermore, our study revealed that engagement in the programme was a deterrent to adolescent antisocial behaviours, as participants were occupied with extramural activities. This finding resonates with prior research emphasizing the role of physical activity in fostering friendships and social bonds among children and adolescents [ 58 , 59 , 60 , 61 ].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, our study revealed that engagement in the programme was a deterrent to adolescent antisocial behaviours, as participants were occupied with extramural activities. This finding resonates with prior research emphasizing the role of physical activity in fostering friendships and social bonds among children and adolescents [ 58 , 59 , 60 , 61 ].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, reduced time in PA engagement or exclusion of PA engagement was linked to frustration, resulting in higher levels of acting out behaviors ( Kjønniksen et al., 2009 ). Conversely, previous meta-analytical studies indicated that the PA intervention programs (e.g., physical exercise, PA and mind-body interventions, and martial arts) effectively improved externalizing behaviors (e.g., aggression, delinquency, hostility, anger, and other maladaptive or disruptive behaviors) in both minors (children and adolescents) and adults ( Harwood et al., 2017 ; Spruit et al., 2016 ; van der Sluys et al., 2022 ). Thus, meeting at least two components of 24-HMB guidelines could optimize its associations with externalizing behaviors among our target population.…”
Section: Discussionmentioning
confidence: 85%
“…The Centers for Disease Control and Prevention in the USA recommends that children with ADHD should manage their symptoms and maintain health by engaging in physical activity, limiting screen time, and ensuring sufficient sleep [ 42 ]. These strategies are also effective not only in managing hyperactive behavior, but also in promoting overall well-being [ 32 , 33 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%